2012
DOI: 10.1159/000341550
|View full text |Cite
|
Sign up to set email alerts
|

Good Penetration of Moxifloxacin into Human Abscesses

Abstract: Abscesses are often treated with antibiotics in addition to incision or when incision is unfeasible, but accurate information about antibiotic abscess penetration in humans is missing. This study aimed at evaluating the penetration of moxifloxacin into human abscesses. After administration of a single dose of 400 mg moxifloxacin, drug concentrations were measured in 10 differently located abscesses at incision, and in plasma over 8 h. At incision performed 0.9–4.8 h after administration, moxifloxacin concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Abscesses are composed of an outer fibrotic wall, an inner layer of leukocytes, and a central area of necrotic debris . Penetration of antibiotics into an abdominal abscess is highly variable and unpredictable . Additionally, the acidic environment within an abscess, where pH ranges from 5.5–7.2 can also change antibiotic activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Abscesses are composed of an outer fibrotic wall, an inner layer of leukocytes, and a central area of necrotic debris . Penetration of antibiotics into an abdominal abscess is highly variable and unpredictable . Additionally, the acidic environment within an abscess, where pH ranges from 5.5–7.2 can also change antibiotic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that abscesses likely lack active transport, and thus the equilibrium of antibiotics between serum and abscess fluid will be attained relatively slowly due to passive diffusion . However, eventually the free concentrations of antibiotics within the abscess will be equal or higher to that in serum concentration because antibiotics inside the abscess are not being metabolized or excreted . This form of antibiotic trapping is believed to favor time‐dependent antibiotics, such as β‐lactams, whose bactericidal effectiveness is optimized when the time of bacterial exposure to the antibiotic is maximized .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations